VALUES CONTAINED IN THE BADEWA TRADITIONAL CEREMONY OF THE COMMUNITY IN BERANGAS TIMUR VILLAGE, ALALAK SUB-DISTRICT, BARITO KUALA REGENCY IN 1998–2010: Nilai-Nilai Yang Terkandung Dari Upacara Adat Badewa Masyarakat Desa Berangas Timur Kecamatan Alalak Kabupaten Barito Kuala Tahun 1998–2010 - Tantawi jauhari, Rabiatul nita; Melisa Prawitasari; Sriwati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the Badewa traditional ceremony as an alternative healing practice among the Dayak Bakumpai community in Berangas Timur Village, Alalak Subdistrict, Barito Kuala Regency, South Kalimantan. Thebadewa ritual represents a cultural tradition rooted in spiritual and social values that has long served as a community-based healing method. The research aims to examine the background, existence, and cultural values of the badewa ceremony during the period 1998–2010. A historical method was employed, involving four key stages: heuristics (data collection through interviews, literature studies, and field observations), source criticism (both internal and external), interpretation, and historiography (historical writing). Findings indicate that badewa has existed since before the arrival of Islam in South Kalimantan. In 1998, the practice was reintroduced to Berangas Timur by the family of H. Idrus from Marabahan and began to gain recognition as an alternative healing option. Despite a decline in public interest after 2010, the ritual continues to be preserved through intergenerational transmission and annual large-scale performances. The novelty of this research lies in documenting and analyzing a local healing tradition that integrates spiritual beliefs with community solidarity. The badewa ceremony not only offers alternative medical treatment but also functions as a medium for cultural preservation and identity reinforcement within the Bakumpai community.